2020
DOI: 10.1111/jocs.15160
|View full text |Cite
|
Sign up to set email alerts
|

Robotic‐assisted cardiac surgery without aortic cross‐clamping: A safe alternative approach

Abstract: Background and Aim: Attempting to place an aortic cross-clamp may complicate surgery and postoperative outcomes in patients who have mediastinal adhesions or in those with extensive aortic calcification. Although right-sided cardiac surgery via thoracotomy is not a new technique in these patients, robotic-assisted intracardiac repair without cross-clamping was not reported in a large group of patients previously. In this study, the safety of robotic-assisted cardiac surgery without aortic cross-clamping was ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 5 publications
0
20
0
Order By: Relevance
“…Although previous sternotomy and thoracotomy are considered relative contraindications for robotic surgery, robot-assisted reoperations can be successfully performed. [ 3 , 6 ] For redo operations, main goals of robotic surgery are to avoid sternotomy, to use highly mobile instruments, to enable high-definition visualization, and to decrease CPB time by operating on the "target field only". In this regard, aortic cross-clamping (ACC) is a major problem due to dense adhesions around the aorta that cannot be dissected with a robotically approach.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although previous sternotomy and thoracotomy are considered relative contraindications for robotic surgery, robot-assisted reoperations can be successfully performed. [ 3 , 6 ] For redo operations, main goals of robotic surgery are to avoid sternotomy, to use highly mobile instruments, to enable high-definition visualization, and to decrease CPB time by operating on the "target field only". In this regard, aortic cross-clamping (ACC) is a major problem due to dense adhesions around the aorta that cannot be dissected with a robotically approach.…”
Section: Discussionmentioning
confidence: 99%
“…Ventricular fibrillation (VF) of the heart is another option instead of ACC. [ 3 ] It is obviously a good alternative and may safely be used in daily practice for these patients. On the other hand, many authors have concluded that myocardial energy consumption reaches its highest level in VF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In conclusion, robot-assisted cardiac surgery without aortic cross-clamping may provide an alternative approach in patients with severe aortic calcification or mediastinal adhesions. [ 5 ] However, the most important issues to be taken into consideration during the operation are the avoidance of left ventricular distention and air embolism.…”
Section: Case Reportmentioning
confidence: 99%
“…With increased acceptance of robotic assistance in cardiac surgery, it was only time before nonarrested heart surgery would find its use in this technique also. In this issue of the Journal of Cardiac Surgery , Gullu et al 5 report on 25 patients who underwent predominantly mitral valve and/or tricuspid valve surgery without cardioplegia. The indications for this approach were porcelain aorta or previous surgery making for a difficult and dangerous mediastinal dissection.…”
mentioning
confidence: 99%